Responsibilities of Muslim women - Yasin, Khalid; One Islam Production (N.S.W, Australia : One Islam Productions, 2006)
In this lecture, Khalid Yasin points out the common issues Muslim women have in their daily lives a mother, wives and women in the community. He gives advice on how to deal with such issues
Title from title screen
Presenter : Khalid Yasin
Keywords: Women in Islam; Women, Muslim